Individual patient data meta-analysis of allogeneic peripheral blood stem cell transplant vs bone marrow transplant in the management of hematological malignancies: indirect assessment of the effect of day 11 methotrexate administration. - Bensinger, W (2006)
The effects of immunosuppressive regimens on the outcomes of patients with hematological malignancies undergoing allogeneic stem cell transplantation remain uncertain. We conducted an individual patient data meta-analysis using data from nine randomized trials comparing allogeneic peripheral blood stem cell (PBSCT) transplants to bone marrow (BMT) transplants, focusing on the administration of three vs four doses of methotrexate (MTX) as part of a regimen for graft-versus-host-disease (GVHD) prophylaxis which included cyclosporine. Six trials containing 573 patients prescribed four doses of MTX while three trials containing 534 patients prescribed three doses of MTX. Four doses of MTX conferred a statistically significant survival advantage, resulting in death odds ratio (OR) 0.67 (CI 0.52-0.88) (P=0.0036) for recipients of PBSC compared to BM; with three doses, there was no statistically significant difference. In the four-dose studies relapse rates were 36.6% among recipients of BM compared to 19.2% among recipients of PBSC (P=0.0015). The rates of relapse in the three dose studies were 26% for both PBSC and BM. We hypothesize that the fourth dose of MTX provides extra immunosuppression among BM recipients resulting in a reduced anti-leukemic effect. This hypothesis can only be proved or disproved by a prospective, randomized trial.